2018
DOI: 10.1038/s41467-018-06429-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant neighbor detection and allelochemical response are driven by root-secreted signaling chemicals

Abstract: Plant neighbor detection and response strategies are important mediators of interactions among species. Despite increasing knowledge of neighbor detection and response involving plant volatiles, less is known about how soil-borne signaling chemicals may act belowground in plant–plant interactions. Here, we experimentally demonstrate neighbor detection and allelopathic responses between wheat and 100 other plant species via belowground signaling. Wheat can detect both conspecific and heterospecific neighbors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
217
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(220 citation statements)
references
References 60 publications
3
217
0
Order By: Relevance
“…In addition to regulating plant physiological and morphological responses [12,13], a growing number of studies have demonstrated that these phytohormones also sculpt the root microbiome [14,15]. For instance, the secretion of root salicylic acid (SA) is involved in plant neighbour detection and shapes the root microbiome by modulating taxonomic groups of bacteria [9,10]. Similar functions have been reported for jasmonic acid (JA) and its derivatives [16].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition to regulating plant physiological and morphological responses [12,13], a growing number of studies have demonstrated that these phytohormones also sculpt the root microbiome [14,15]. For instance, the secretion of root salicylic acid (SA) is involved in plant neighbour detection and shapes the root microbiome by modulating taxonomic groups of bacteria [9,10]. Similar functions have been reported for jasmonic acid (JA) and its derivatives [16].…”
Section: Introductionmentioning
confidence: 81%
“…In natural environments, plants constantly adjust the composition and concentration of root metabolites in response to various kinds of biotic stressors, such as neighbour competition, pathogen infection and herbivore attack [5][6][7]. This may result in allelochemical responses to neighbouring plants, reduced plant susceptibility to pathogen attack or the prevention of grazing by herbivores [8,9]. However, relatively few studies have sought to understand the mechanisms and effects of stress-induced root-secreted metabolites on rhizosphere microbiota [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…officinale roots (Huang et al, ). In general, physical (e.g., light and contact), chemical (e.g., volatile and exudates), and biological (e.g., arbuscular mycorrhizal fungi) factors may trigger neighbourhood effects and affect plant growth and defence (Babikova et al, ; Crepy & Casal, ; Erb et al, ; Hu, Robert, et al, ; Kong et al, ; Semchenko, Saar, & Lepik, ; Yang, Callaway, & Atwater, ). As C .…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we found that the presence of C. stoebe enhanced the performance of M. melolontha larvae feeding on T. officinale roots . In general, physical (e.g., light and contact), chemical (e.g., volatile and exudates), and biological (e.g., arbuscular mycorrhizal fungi) factors may trigger neighbourhood effects and affect plant growth and defence (Babikova et al, 2013;Crepy & Casal, 2015;Erb et al, 2015;Hu, Robert, et al, 2018;Kong et al, 2018;Semchenko, Saar, & Lepik, 2014;Yang, Callaway, & Atwater, 2015). As C. stoebe constitutively releases large amounts of sesquiterpenes into the rhizosphere , we hypothesized that root VOCs may be responsible for the plant- Plant VOCs can influence herbivore performance directly or indirectly by changing the chemistry of receiver plants (Engelberth et al, 2004;Erb et al, 2015;Huang et al, 2018;Sugimoto et al, 2014;Veyrat, Robert, Turlings, & Erb, 2016;Ye et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that loliolide induced resistance to multiple herbivore pests, such as the two-spotted spider mite (Tetranychus urticae), western flower thrips (Frankliniella occidentalis), and common cutworm (Spodoptera litura), through the activation of JA-independent defense responses [5]. Loliolide has also been shown to function as an allelochemical in plant-plant communications [6,7]. Loliolide is produced via the chemical or enzymatic degradation process of α-carotene and β-carotene [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%